ANALISIS KUALITAS AIR WADUK RIO – RIO DENGAN METODE INDEKS PENCEMARAN DAN TEKNOLOGI UNTUK MENGURANGI DAMPAK PENCEMARAN - Hartaja, Dinda Rita K. (Jurnal Air Indonesia, 2015)
Waduk Rio – Rio is an artificial ponds located in East Jakarta. Current condition of the waduk rio - rio is not maintained, its visible from outlet of the ponds foaming indicates pollution. Therefore, monitoring the quality of the ponds which describes the condition of good quality ponds in physics, chemistry, and microbiology. The results of the monitoring and analysis data using the pollution index, it can be seen that the pollution level of Waduk Rio - Rio in the first period (dry season) classified as moderate polluted by pollution index value of 5.542. While in the second period (transitional season), the value of the pollution index at 11.069 and classified as heavy polluted. The pollution sources of Waduk Rio - Rio is domestic wastewater which comes from community activities around the ponds. It can be seen from the high biological parameters such as Fecal Coli and Coliform. In order to reduce the level of pollution in the Waduk Rio - Rio, the domestic wastewater discharged into the ponds needs to be processed first. One of the domestic wastewater treatment technology is a biofilter Anaerobic - Aerobic. Keywords : Pollution Indeks, Water Quality Indeks, Biofilter Anaerob – Aerob